Dimethylsulphoxide Complexes of Vanadium(III) - Sirat, Kamaliah; W.Smith, Peter (1992)
Dimethylsulphaxide(DMSO) compkxsalts of vanadium(IIl) with theemfrincalformulae VCI,. 6DMSOand VBr,. 6DMSO were synthesized and investigated. The observed infra-red band positions of the v(S.O) stretch indicate that the ligand is coordinated to ·vanadium ion via oxygen. Far-infra-l-ed spectra lead to the conclusion that no-1U of the halide ions are eoen·dinated to the metal ion. Diffuse reflectance spectra are consistent with vanadium in an octahedral environment. Accordingly, the chlarideand bromide salts areformulated as [V(DMSO)jCI, and [V[DMSOljBrp respectively